Increasing the Empowerment of Ngesti Utomo Farmer Groups through Business Management Training - Ariyani Wahyu Wijayanti; Ali Mursyid Wahyu Mulyono; Ludfia Windyasmara; Muhammad Husein; Made Wedaswari; Anis Sri Hastuti; Angella Giri Anjani (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT Improving farm business management capacity is an important effort to support the sustainability of farming activities and farmer welfare. This community service program aimed to improve the business management capacity of the Ngesti Utomo Farmer Group in Wonogiri Regency through farm business management training. The partner farmer group faced major problems related to weak managerial practices in farm business management, particularly in business planning, business legality, cost of production determination, and marketing. The activity involved 25 members of the farmer group. The implementation method used a group capacity building training approach through interactive lectures and participatory discussions. The training materials covered business motivation, business legality, cost of production determination, business initiation and planning, as well as marketing. Program evaluation was conducted using pre-test and post-test methods to measure changes in participants’ understanding before and after the training. The results showed an increase in scores across all training aspects, indicating improved managerial capacity among participants. The training also encouraged changes in participants’ perspectives toward viewing farming as an economic activity that should be managed in a more planned and sustainable manner. Follow-up activities are directed toward assisting the implementation of farm business management practices to support the sustainability of the farmer group’s business. Keywords: business management, community empowerment, farmer group, training